THE URGENCY OF PROBLEM-SOLVING TRAINING FOR STUDENTS AT SMP N 10 TANJUNG BALAI USING GROUP COUNSELING SERVICES - Syafira, Rika; Lubis, Saiful Akhyar (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to determine the urgency of problem-solving training for students in SMP N 10 Tanjung Balai School by using group counseling services. The research method used is a qualitative method with a descriptive approach. The research sample consists of 12 students, the homeroom teacher, and also the guidance counselor. The data analysis technique used is data reduction, which requires deep thinking insight. After reducing the data, the data is presented and then the researcher draws conclusions. The data validity test technique in this research uses triangulation by asking the same questions to different sources. In general, problem-solving training for students in school is very important because everyone faces problems frequently. From the research conducted, it can be concluded that problem-solving training is very important and has a positive impact on students. Therefore, the researcher wants to conduct research with the title “The urgency of problem-solving training for students in SMP N 10 Tanjung Balai school by using group counseling services”.